68Ga-PSMA PET/CT in Patients With Biochemical Recurrence of Prostate Cancer: A Prospective, 2-Center Study. (August 2018) - Zacho, Helle D.; Nielsen, Julie B.; Dettmann, Katja; Haberkorn, Uwe; Langkilde, Niels C.; Jensen, Jørgen B.; Petersen, Lars J.
Abstract : Purpose of the Report: The aim of this study was to prospectively investigate the detection rate of 68 Ga-PSMA PET/CT in biochemical recurrence (BCR) of prostate cancer and its impact on patient management. Materials and Methods: Patients with BCR after curatively intended treatment of prostate cancer were included. Each patient underwent a 68 Ga-PSMA PET/CT. Changes in patient management based on the results of 68 Ga-PSMA PET/CT were assessed. Results: Seventy patients were included. Sixty-four patients (91%) had radical prostatectomy, of whom 17 patients (24%) received salvage radiation therapy due to first biochemical relapse. Six patients (9%) underwent radiation therapy as the primary treatment. 68 Ga-PSMA PET/CT detected recurrent disease in 37 patients (53%). The detection rate was 22% for prostate-specific antigen (PSA) levels up to 0.5 ng/mL compared with 83% for PSA levels greater than 0.5 ng/mL. Pathological uptake of 68 Ga-PSMA was observed in 4 (16%) of 21, 4 (44%) of 9, 0 of 1, 7 (70%) of 10, and 22 (88%) of 25 patients with PSA levels from 0.2 to 0.3 ng/mL, 0.31 to 0.4 ng/mL, 0.41 to 0.5 ng/mL, 0.51 to 1 ng/mL, and greater than 1 ng/mL, respectively. Prostate-specific antigen was significantly higher in PSMA-positive patients than in PSMA-negative patients. In 15 (22%) of 69 patients, the results caused a definite change in patient management, and in another 15 (22%) of 69 patients, 68 Ga-PSMA PET/CT guided the choice of treatment. Conclusions: 68 Ga-PSMA PET/CT detects lesions in a large proportion of patients with BCR. Detection rates at low PSA levels (<0.5 ng/mL) were notably below the values reported in previous retrospective studies; however, detection rates improved with increasing PSA levels.